Sustaining social balance and peace in the Post-COVID-19 - Bendebka, Ramzi; Shogar, Ibrahim Adam Ahmed; Fettane, Amar (2022)
The spread of COVID-19 disease since the end of 2019 has led to social functions and activities disorders in our societies. The pandemic has a significant influence on social balance and peace. This situation has arisen awareness that a more sustainable model is needed. The study assumes that the Maqasid al-Shariah approach can provide comprehensive social sustainability and protection solutions. Therefore, we offer analyses of the social dimensions during the disease and its impact on balance and peace, evaluate authorities' role in providing solutions to current issues and problems, and determine the possible answers based on the Maqasid al-Shariah approach.